Secondary School EFL Teachers’ Knowledge of Self-Regulated Learning (SRL) - Fansuriyah, Ika Yulinda; Muniroh, Siti (Graduate School of Universitas Negeri Malang, 2023)
Self-regulated learning (SRL) is an important skill to acquire for students because it helps students to have a better academic achievement, study skills, self-efficacy, and learning motivation in a learning process. Teachers are required to have high level of knowledge about SRL to be able to teach SRL to their students. Thus, this study was aimed to examine teachers’ knowledge of SRL. This study employed a quantitative method using survey design involving 42 EFL teachers from junior and secondary schools in two districts in Gresik Regency. A knowledge test to measure teachers’ content knowledge of SRL (SK-SRL) and pedagogical content knowledge of SRL (PCK-SRL) was administered to collect the data. The result of this study showed that EFL teachers hold a moderate level of knowledge of SRL. This means that EFL teachers understand the general concept of SRL, various types of SRL strategies such as cognitive, metacognitive, and motivation as well as emotion strategies. Moreover, teachers also understood about the three-cyclical phases of SRL which were the forethought, monitoring, and evaluation phase as well as various activities in each phase. However, they still need more insight about how to diagnose students’ SRL competence and skills, and need to explore more various ways to teach SRL to their students.